The Right to Privacy in the Age of Artificial Intelligence - Reema Ahmad Alharbi (International Journal of Law Research and Studies, 2026)
This research aims to clarify the conceptual framework of the right to privacy and its relationship to artificial intelligence (AI). It employs an analytical study that defines the concept of the right to privacy and its legal nature, then explains the concept of AI, its characteristics, types, and mechanisms of operation. The study also highlights the impact of technological advancements on reshaping the concept and limits of the right to privacy. The importance of this research stems from the increasing use of AI technologies and their associated collection, processing, and analysis of vast amounts of personal data. The research adopts an analytical approach by studying and analyzing the legal concepts related to the right to privacy and AI, and by explaining the data-driven and algorithm-based mechanisms of AI. It also utilizes a historical approach to trace the historical development of the right to privacy. The research concludes that the right to privacy is no longer limited to its traditional meaning and the protection of private life but has expanded to include personal data. Furthermore, it demonstrates that AI, with its inherent characteristics and capabilities, expands its impact on the right to privacy. This necessitates achieving a balance between technological development and the protection of human rights, particularly the right to privacy